A case report of the metagenomic next-generation sequencing for timely diagnosis of a traveler with nonspecific febrile Q fever - Qiaoli Xu; Wenyan Han; Yihua Cai; Yuyao Yin; Yifan Guo; Hongbin Chen; Hui Wang (Heliyon, 2024)
Q fever is a worldwide distribution disease caused by Coxiella burnetii（C. burnetii）, an obligate intracellular, Gram-negative acidophilic bacterium belonging to γ-proteobacterium. Most patients present with acute Q-fever accompanied by atypical flu-like symptoms, with only 1%–5% of cases may develop into persistent and focally infected foci, mainly manifest as endocarditis, osteomyelitis and prosthetic arthritis. In this case, the patient experienced an unexplained and uninterrupted fever up to 39.2 °C for a week, accompanied by chills and headaches, as well as abnormal liver function. The laboratory reported negative results for blood culture and respiratory-associated pathogens, however, the metagenomic next-generation sequencing (mNGS) reported that detection of 20 sequence reads of C. burnetii in the patient's peripheral blood. In addition, the patient had traveled to Sri Lanka, Iraq and Saudi Arabia before illness. In clinical, the treatment regimen was adjusted from empirically intravenous moxifloxacin 400 mg a day for 1 week to continuously oral minocyline 100 mg twice daily for 2 weeks. The patient was in good health without any adverse sequelae during outpatient visitation and the phone calls follow-up. In conclusion, the mNGS does provide an early and timely diagnostic basis for rare and difficult to culture pathogens, which contributes to the success of clinical anti-infection.